Analyzing Speech Accommodation Model in 1st Debate of the 2024 Indonesian Presidential Candidates - Muhid, Abdul (Universitas Pendidikan Mandalika, 2024)
In Indonesia, candidates, especially presidential candidates, are busy crafting positive narratives to build a positive image. In this study, we will look at language use from the macro level, namely, the situation and function of communication, as well as at the micro level, which is how the verbal interactions of language users communicate their ideas in front of the public. The current article uses qualitative with descriptive and interpretative types. Analysis of the Speech Accommodation Model in the first debate of the 2024 Indonesian presidential candidates reveals several key insights into how candidates strategically adapt their language to connect with different audiences and achieve their communication goals. The analysis highlights the dynamic nature of accommodation, with candidates shifting their linguistic styles based on situational factors, such as the topic of discussion, the perceived attitudes of the audience, and the rhetorical strategies employed by their opponents. This research provides valuable insights into the complex interplay between language, identity, and power in political communication. By examining how candidates navigate linguistic diversity and negotiate their rhetorical stance, we acquire a deeper understanding of the strategies employed to engage, persuade, and mobilize voters in pursuing electoral success. And detail model used by all candidates is summed up as follows; inward convergence, outward convergence, divergence, con in dive accommodation, and over-accommodation.